Pengaruh Disiplin Belajar, Kecerdasan Intelektual, Kecerdasan Emosional, Teman Sebaya dan Perhatian Orang Tua Terhadap Prestasi Belajar Ekonomi Siswa Kelas X di SMAN 1 Sungai Limau - Yussyah, Leli; Rosya, Nilmadesri; Verawati, Rika (CV. ITTC INDONESIA, 2025)
This study aims to analyze: 1) the influence of learning discipline on learning achievement, 2) the influence of intellectual intelligence on learning achievement, 3) the influence of emotional intelligence on learning achievement, 4) the influence of peers on learning achievement, 5) the influence of parental attention on learning achievement, 6) the influence of learning discipline, intellectual intelligence, emotional intelligence, peers and parental attention together on learning achievement. The type of research used in this study is quantitative research. The results of the study indicate that Learning Discipline has a positive and significant effect on Learning Achievement, this can be seen from the coefficient value of 0.145. The results of the t-test show that learning discipline has a t-count value of 3.014> t-table of 1.66. Intellectual Intelligence has a positive and significant effect on Learning Achievement, this can be seen from the coefficient value of 0.230. The results of the t-test show that intellectual intelligence has a t-count value of 2.509> t-table of 1.66. Emotional Intelligence has a positive and significant effect on Learning Achievement, this can be seen from the coefficient value of 0.482. The results of the t-test show that emotional intelligence has a t-count value of 3.146> t-table of 1.66. Peers have a negative and significant effect on Learning Achievement, this can be seen from the coefficient value of -0.299. The results of the t-test show that peers have a t-count value of -6.590 <t-table of 1.66. Parental Attention has a positive and significant effect on Learning Achievement, this can be seen from the coefficient value of 0.149. The results of the t-test show that parental attention has a t-count value of 2.446> t-table of 1.66. Learning Discipline, Intellectual Intelligence, Emotional Intelligence, Peers and Parental Attention simultaneously have a positive and significant effect on Learning Achievement, this can be seen from the F-count value of 13.306> 2.47 F-table with a significant value of 0.000 <0.05. So the decision is H0 is rejected and Ha is accepted.